2016
DOI: 10.1021/acs.joc.6b00584
|View full text |Cite
|
Sign up to set email alerts
|

Computational Methods to Predict the Regioselectivity of Electrophilic Aromatic Substitution Reactions of Heteroaromatic Systems

Abstract: The validity of calculated NMR shifts to predict the outcome of electrophilic aromatic substitution reactions on different heterocyclic compounds has been examined. Based on an analysis of >130 literature examples, it was found that the lowest predicted (13)C and/or (1)H chemical shift of a heterocycle correlates qualitatively with the regiochemical outcome of halogenation reactions in >80% of the investigated cases. In the remaining cases, the site of electrophilic aromatic substitution can be explained by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 59 publications
0
40
0
Order By: Relevance
“…Hence, for studies of tautomerism in pyrazoles, measurement of chemical shifts permits accurate identification of the species present in each condition evaluated as well as the ascertainment of tautomer equilibrium constants, upon the adequate treatment of the samples and data [39]. Additionally, it has been shown that NMR data can be used for reactivity predictions in heterocyclic compounds, in light of the development of more efficacious syntheses [85].…”
Section: Experimental Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, for studies of tautomerism in pyrazoles, measurement of chemical shifts permits accurate identification of the species present in each condition evaluated as well as the ascertainment of tautomer equilibrium constants, upon the adequate treatment of the samples and data [39]. Additionally, it has been shown that NMR data can be used for reactivity predictions in heterocyclic compounds, in light of the development of more efficacious syntheses [85].…”
Section: Experimental Studiesmentioning
confidence: 99%
“…In these circumstances, a paramount need to elucidate the precise chemical potential of the entities present in a specific reactant mixture emerges. HOMO and LUMO states and energies of the tautomeric structures represent the parameters that mostly contribute to their chemical potential; as such, variations alter the acidic/basic and electrophilic/nucleophilic properties of the compounds [85,115]. It was already shown that in heterocycles, including 3(5)-aminopyrazoles, the different characteristics of molecular orbitals promote distinct reactivities of each of the tautomeric species [66,85].…”
Section: (5)-aminopyrazole In Heterocyclic Synthesismentioning
confidence: 99%
“…16,17 Later, models using estimated 1 H and 13 C NMR shifts (using ChemDraw's linear additives rules), motivated by the same principle of estimating nucleophilicity, achieved 80% accuracy on a collection of 130 EAS reactions limited to electron rich aromatics and heterocycles. 18 When supplemented with density functional theory (DFT) calculations, 19 the accuracy of predictions was reported to be >95% on the same dataset and formed the basis for a followup semi-empirical quantum mechanical (SQM) method. The SQM model predicts selectivity based on estimated energies of carbocations generated from protonation at each site, meant to represent potential intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…This paper provides a fast, reliable, and easy-to-use computational tool to predict the site selectivity of EAS reactions more robustly than our previously reported NMRbased method. 6 In a broader sense, the ability to block the more reactive site(s) in complex heteroaromatics may increase the use of halogens as protective groups in arene chemistry. 7,8 It was recently reported that empirically calculated 1 H and 13 C chemical shis can be applied to retrospectively account for the regiochemical outcome of ca.…”
Section: Introductionmentioning
confidence: 99%
“…95%. 6 The chemical shis were obtained immediately from the structure using ChemDraw. Conversely, DFT calculations are time-consuming for larger compounds and cannot be performed by non-expert users and there is a certain degree of subjectiveness in predicting the regioselectivity based on the HOMO orbitals.…”
Section: Introductionmentioning
confidence: 99%